National Museum. Key issues and debate - Cabanillas Delgadillo, Virgilio (2017)
We will discuss the need to end a debt that the Peruvian Government owns to the country’s culture: the construction of an appropriate infrastructure for the National Museum in the country’s capital. We will review previous experiences and will check current projects of the Ministry of Culture in Pachacamac. We will propose ideas for other museums required by Lima.